Energy Consumption and Inflation Dynamics in Nigeria: An ARDL Cointegration Approach - Bassey, Godwin Edet; Ekong, Uduak Michael (Energy Economics Letters, 2019)
This paper investigated the dynamic relationship between energy consumption and inflation in Nigeria using time series data obtained for the period 1980 to 2017. Applying Autoregressive Distributed Lag (ADL) technique on the variables, the study found that Premium Motor Spirit (PMS), Dual Purpose Kerosene (DPK) and Natural gas were noninflationary in Nigeria both in consumption and prices over the period. Also, Automotive Gas Oil (AGO) consumption produces strong evidence of positive inflationary pressure but not in prices throughout the study period. Further, we found a strong causality link between natural gas consumption and inflation in Nigeria. We concluded that inflation in Nigeria is not majorly a demand-pull phenomenon, pulled by energy consumption. We provide both subjective and evidence-based reasons for the economic trend and recommend a bridge in the degrading systemic informality in the energy sector that will deliver real time effect of energy consumption-inflation proposition in Nigeria.